ChemInform Abstract: A Facile Synthesis of 3‐Substituted Benzofurans and Indoles Through a Palladium‐Catalyzed Domino Carbopalladation/CH‐Activation/Isomerization Process. Issue 17 (28th April 2014) - Tietze, Lutz F.; Hungerland, Tim; Ammermann, Jonas; Eichhorst, Christoph; Reichmann, Sven O.; Stalke, Dietmar
Abstract Novel benzofurans and indoles (II) are synthesized by a domino carbopalladation/CH‐activation/isomerization process.